PENGARUH PEMBERIAN JUS BUAH BIT DENGAN PENINGKATAN HB PADA REMAJA PUTRI - Zuhraini, Rani; Anggraini, Anggraini; Kurniasari, Devi; Suharman, Suharman (MIDWIFERY JOURNAL, 2021)
Backgrund :The prevalence of anemia in Indonesia is 21.7%. The prevalence of anemia in women is higher than in men. Based on the results of a pre survey conducted on 6 female students of Bandar Lampung 14 high school about adolescent anemia, it was found that 4 respondents (60%) did not understand well what anemia was in adolescents, and there were anemia symptoms such as anemic, weak, tired, lethargic, after hemorrhoid examination. Hb values are varied, which is 8.5-10.6 mg / dl while the remaining 2 people (20%) can understand anemia in adolescent anemia, and do not find anemia symptoms in these students. The purpose of this study is to know the effect of giving beet juice with increased Hb in adolescent girls at SMAN 14 Bandar Lampung in 2019Purpose :It is known that there is an effect of giving beet juice with an increase in Hb in girls in SMAN 14 Bandar Lampung in 2019Methode :Quasi Experimental research design with one group pretest - posttest design approach. The population in this study was the first and second grade teenage girls at SMAN 14 Bandar Lampung in 2019 as many as 49 people. The sampling technique uses purposive sampling technique. The independent variable (independent) is beet juice, while the dependent variable is the Hb level, univariate data analysis to determine the average hemoglobin level before and after administration of beet juice, bivariate data analysis using T-test dependent test.Result :The results of this study are known that the average Hb in adolescent girls before being given beetroot juice is equal to 10.682 gr / dl. The average after being given beet juice is 11,088 gr / dl. It is known that there is an effect of giving beet juice with an increase in Hb in adolescent girls at SMAN 14 Bandar Lampung in 2019, t test was obtained (p value 0.001 <a 0.05). Suggestions in this study are for young women to consume beet juice as a way to increase hemoglobin levels.Conclusion :There is an effect of giving beet juice with an increase in Hb in girls in SMAN 14 Bandar Lampung in 2019Suggestions are expected to consume 250 ml of beetroot juice 1 time / day, for 7 days to overcome the occurrence of anemia. Keywords            : Beet juice, Adolance, Haemaglobin ABSTRAK : PENGARUH PEMBERIAN JUS BUAH BIT DENGAN PENINGKATAN HB PADA REMAJA PUTRI DI SMAN 14 BANDAR LAMPUNG TAHUN 2019Latar Belakang :Prevalensi anemia diIndonesia yaitu 21,7%. Prevalensi anemia pada perempuan lebih tinggi dibanding laki-laki. Berdasarkan hasil pre survey yang dilakukan terhadap 6 siswi SMA 14 Bandar Lampung tentang anemia remaja, didapat 4 responden (60%) tidak memahami dengan baik apa anemia pada remaja, dan terdapat gejala anemia seperti anemis, lemah, letih, lesu, setelah dilakukan pemeriksaan Hb didapat nilai Hb yang bervariasi yaitu 8.5-10.6 mg/dl sedangkan 2 orang sisanya (20%) dapat memahami anemia pada anemia remaja, dan tidak ditmukan gejala anemia pada siswi tersebut. Tujuan dari penelitian ini adalah diketahui ada pengaruh pemberian jus buah bit dengan peningkatan Hb pada remaja putri di SMAN 14 Bandar Lampung Tahun 2019Tujuan :Diketahui ada pengaruh pemberian jus buah bit dengan peningkatan Hb pada remaja putrid di SMAN 14 Bandar Lampung Tahun 2019Metode :Rancangan penelitian Quasi Eksperimental dengan pendekatan one group pretest – posttest design. Populasi dalam penelitian  ini adalah remaja putri kelas 1 dan 2 di SMAN 14 Bandar Lampung Tahun 2019 sebanyak 49 orang. Teknik pengambilan sampel menggunakan teknik purposive sampling. Variabel bebas (independen) yaitu Jus buah bit, sedangkan variabel terikat (dependen) yaitu Kadar Hb, analisa data univariat untuk mengetahui rata-rata kadar hemoglobin sebelum dan setelah pemberian jus buah bit, analisa data bivariat menggunakan uji T-test dependent.Hasil :Hasil penelitian ini adalah diketahui rata-rata Hb pada remaja putri sebelum diberikan jus buah bit yaitu sebesar 10,682 gr/dl. Rata-rata sesudah  diberikan jus buah bit sebesar 11,088 gr/dl. Diketahui ada pengaruh pemberian jus buah bit dengan peningkatan Hb pada remaja putri di SMAN 14 Bandar Lampung Tahun 2019, uji t didapat (p value 0,001 <a 0.05). Kesimpulan :Ada pengaruh pemberian jus buah bit dengan peningkatan Hb pada remaja putrid di SMAN 14 Bandar Lampung Tahun 2019Saran diharapkan untuk mengkonsumsi jus buah bit 1 kali/ hari sebanyak 250ml, selama 7 hari untuk mengatasi terjadinya anemia.  Kata Kunci          : Jus buah bit, Remaja, Hemaglobin